(untitled) (Research, Society and Development, 2020)
The objective of this research is to know the experiences of adolescents with HIV infection and their perspectives for improving health care. Qualitative, descriptive and exploratory research. To collect the data, a group interview was conducted. This occurred in a Non-Governmental Organization (NGO) and a Public Hospital located in Porto Alegre, State of Rio Grande do Sul / Brazil. The participants were 18 adolescents from 13 to 19 years old. Thematic Content Analysis was used to interpret the information. The results were expressed in categories: Sexuality in adolescence: spaces for dialog and accountability for condom use; Use of medicines: strategies and perspectives for improving care; and Prejudice and discrimination: protection measures. The adolescent signals their experiences and perspectives, which contributes to the improvement of their health and makes it possible to transform, implement and strengthen care practices. Therefore, the convergence of public health and education policies at different levels is essential.